The impact of corporate social responsibility on the cost of equity: an analysis of Vietnamese listed companies - Xuan Quynh Le; Ngoc Tien Nguyen; Thy Ha Van Le (My University, 2019)
The impact of corporate social responsibility on the cost of equity: an analysis of Vietnamese listed companies
Keywords: CSR; Cost of equity; Vietnam